2020
DOI: 10.3390/ijms21041379
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Gas Plasma and Radiotherapy Has Immunostimulatory Potential and Additive Toxicity in Murine Melanoma Cells in Vitro

Abstract: Despite continuous advances in therapy, malignant melanoma is still among the deadliest types of cancer. At the same time, owing to its high plasticity and immunogenicity, melanoma is regarded as a model tumor entity when testing new treatment approaches. Cold physical plasma is a novel anticancer tool that utilizes a plethora of reactive oxygen species (ROS) being deposited on the target cells and tissues. To test whether plasma treatment would enhance the toxicity of an established antitumor therapy, ionizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 66 publications
3
31
0
Order By: Relevance
“…It is conceivable that gas plasma treatment may not only be used for tumor patient palliation, but also as adjuvant or neo-adjuvant therapy during radiotherapy or chemotherapy. This way, the tumor cells might be targeted by several mechanisms simultaneously, as we have recently demonstrated experimentally in other types of cancer cells [72][73][74].…”
Section: Clinical Studiesmentioning
confidence: 87%
“…It is conceivable that gas plasma treatment may not only be used for tumor patient palliation, but also as adjuvant or neo-adjuvant therapy during radiotherapy or chemotherapy. This way, the tumor cells might be targeted by several mechanisms simultaneously, as we have recently demonstrated experimentally in other types of cancer cells [72][73][74].…”
Section: Clinical Studiesmentioning
confidence: 87%
“…Already in 2009, a proof-of-concept study suggested additive cytotoxicity of antibody-conjugated gold nanoparticles with plasma treatment against human YD-9 SCC cells in vitro based on results they have obtained with melanoma cells [ 102 ]. Promising results were seen in the combination of plasma therapy with traditional agents in melanoma treatment [ 103 , 104 , 105 ], which warrants further exploration for research on SCC in the future. This might also relate to combining plasma therapy with other physical modalities, such as pulsed electric fields, as recent reports have shown additive toxicity of both treatments in vitro [ 101 , 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the different in vitro studies, two ways of increasing an anti-tumor immune response are investigated: i) changing the tumor cells' expression of pro-immunogenic molecules, and ii) stimulating immune cells to differentiate and initiate an immune response [1,106]. Several studies have shown that treatment with directly applied gas plasma [107][108][109] or dielectric barrier discharge (DBD) [110][111][112] can increase the immunogenicity of tumor cells. In particular, the ER-chaperon calreticulin (CRT) is proposed to have a significant impact on the tumor cells' immunogenicity [113].…”
Section: Mechabisms Of Action and Selection Of Suitable Liquidsmentioning
confidence: 99%